Is Hysteroscopy Better than Ultrasonography for Uterine Cavity Evaluation? An Evidence-Based and Patient-Oriented Approach. Issue 3 (July 2016) - Di Spiezio Sardo, Attilio; Calagna, Gloria; Laganà, Antonio Simone; Vitale, Salvatore Giovanni; Catena, Ursula; Scutiero, Gennaro; Nappi, Carmine
Evaluation of the uterine cavity is an important part of the gynecological check, especially in symptomatic women and, over the last few decades, a number of technical and technological advancements has allowed a superb investigation of this organ. Traditionally, transvaginal ultrasound (TVUS) has been the first-line diagnostic tool for evaluating uterine diseases, also considering that gynecologists are familiar with the technique since it is included in the basic training in obstetrics and gynecology. Nevertheless, to date "office hysteroscopy" received growing attention since the development of smaller-diameter hysteroscopes which has made it possible to easily perform the hysteroscopy in ambulatory settings, obviating the need for anesthesia and dilatation of the cervical canal. According to our overview, none of the available methods for endometrial evaluation are ideal and each one has pros and cons. TVUS allows assessment of both the myometrium and the endometrium and typically offers greater patient comfort, but it has a higher false-negative rate in diagnosing focal intrauterine pathology. On the other hand, office hysteroscopy has the advantage of providing (most of the time) a real-time diagnosis avoiding anxiety, inconvenience and costs associated with follow-up appointments. The main advantage of the office hysteroscopy on the TVUS is the possibility to perform an operative phase if necessary during the examination itself. In fact, the modern smaller-diameter hysteroscopes have a working channel through which operative miniaturized instruments (mechanical instruments or bipolar electrodes) can be introduced, allowing the performance of target-eye biopsies and the "instant" treatment of most of uterine diseases in outpatient settings.